Exploring the Relationship Between Neighborhood-Built Environment and Elderly Health: A Research Based on Heterogeneity of Age and Gender Groups in Beijing - Li, Jingwei; Tian, Li; Ouyang, Wei (Frontiers in Public Health, 2022)
Background The built environment quality of neighborhoods has a significant impact on the health of the elderly. Although there has been a wealth of studies on low-density Western cities, research on the impacts of built environment on elderly health in high-density Chinese cities is far from sufficient. The pathways by which the built environment affects elderly health remain to be observed, particularly whether such pathways vary for different ages and genders. Methods Based on the data of the “Fourth Survey on the Living Conditions of the Elderly in China” in 2015, a sample survey of 3,360 older adults, aged 60 years and over, in Beijing was conducted. We first explored the built environment factors that affect elderly health with a multilevel regression model. We then adopted a multilevel structural equation model (MSEM) to reveal the mediating effect of health activities. Moreover, a stratified analysis was applied to explore the impact of age and gender heterogeneity on the relationship between built environment and elderly health. Results (1) Neighborhood-built environment measured within a 500 m buffer area had a higher correlation with elderly health when compared with other areas. (2) Physical activity and social interaction played a mediating role in the correlation between the built environment and elderly health. Even if the interference of residential self-selection was controlled within the subgroups, majority of the built environment elements had significant impacts on elderly health. (3) The impacts of built environment variables on elderly health vary among different age and gender groups. Population density mainly promoted elderly health through health activities in the middle-aged (aged 70–79) group and high-aged (aged 80+) group, and shorter distance to transit stations affects health by promoting the social interaction among high-aged males (aged 80+) group compared to with other groups, and high-quality built environment significantly promotes physical activity to alleviate loneliness only in elderly females. Conclusion To effectively boost elderly health by improving the quality of the built environment, adequate considerations should also be given to the differentiated demands of adults of different age and gender groups, precise health behavior interventions should be provided, and the construction of personalized aging-friendly and livable spatial environments should be emphasized to realize healthy and active aging.